COGNITIVE IMPAIRMENT IN PARKINSON’S DISEASE: Early Diagnosis and Ways to Correct - Okhunova, D.A.; Rakhimbaeva , G.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
An urgent problem of neurology is the improvement of diagnostics and correction of cognitive impairment in Parkinson’s disease and Parkinsonism syndromes. On the basis of a comprehensive study, including clinical, laboratory and psychometric data, the results of CT, MRI, angiography of cerebral vessels, computed electroencephalography, the features of cognitive impairment in Parkinson’s disease and vascular parkinsonism were studied. Particular attention among the syndromes of parkinsonism is paid to vascular parkinsonism, the pathogenetic mechanisms of which are still insufficiently studied. Recommendations have been developed to improve the diagnosis and correction of cognitive disorders in Parkinson’s disease and vascular parkinsonism.